El turismo deportivo en Bogotá y sus espacios (2022)
The large-capacity sports venues n Bogotá, which are used  for leisure activities and high-performance sporting events, are places of social use in which there are no specialized inventories for this purpose. Therefore, the objective of this work is to establish the distribution of spaces available or suitable for sports tourism within Bogotá, in order to propose a classification that considers their capacity and uses for these purposes. The expected findings is to have a detailed and organized opinion of the diversity of sports spaces offered by Bogotá D.C. and the different areas of the country, reviewing their significant changes so that citizens can see in retrospect how these spaces have advanced. In conclusion, it is expected to clarify whether these spaces are suitable for the development of sports tourism, seeking the awareness of the fan or visitor and the real use of the property.